ANTICOAGULANT THERAPY IN ACUTE CORONARY SYNDROMES AND ISCHEMIC STROKE - Cichoń, Natalia; Lach, Dominika; Saluk-Bijak, Joanna; Bijak, Michał (Prospects in Pharmaceutical Sciences, 2017)
Cardiovascular diseases, including acute coronary syndromes and ischemic stroke, present a serious problem to modern medicine. In Europe, they lead to 4 million deaths each year. In both diseases the main cause of ischemia is vascular occlusion. Therefore, treatment relies on drugs with a similar antithrombotic action, and includes antiplatelet and anticoagulant therapy. Anticoagulants are used to prevent thromboembolic events by inhibiting the activity of enzymes of the coagulation cascade. They include: vitamin K antagonists, thrombin inhibitors (indirect and direct) and inhibitors of factor Xa. In this paper, the current state of the field of anticoagulant therapy is discussed, as it pertains to patients with acute coronary syndrome and ischemic stroke. In addition, the differences and similarities in the treatment algorithms for these conditions are described.